Controlling Residual Lithium in High‐Nickel (>90 %) Lithium Layered Oxides for Cathodes in Lithium‐Ion Batteries. Issue 42 (31st August 2020) - Seong, Won Mo; Cho, Kwang‐Hwan; Park, Ji‐Won; Park, Hyeokjun; Eum, Donggun; Lee, Myeong Hwan; Kim, Il‐seok Stephen; Lim, Jongwoo; Kang, Kisuk
Abstract: The rampant generation of lithium hydroxide and carbonate impurities, commonly known as residual lithium, is a practical obstacle to the mass‐scale synthesis and handling of high‐nickel (>90 %) layered oxides and their use as high‐energy‐density cathodes for lithium‐ion batteries. Herein, we suggest a simple in situ method to control the residual lithium chemistry of a high‐nickel lithium layered oxide, Li(Ni0.91 Co0.06 Mn0.03 )O2 (NCM9163), with minimal side effects. Based on thermodynamic considerations of the preferred reactions, we systematically designed a synthesis process that preemptively converts residual Li2 O (the origin of LiOH and Li2 CO3 ) into a more stable compound by injecting reactive SO2 gas. The preformed lithium sulfate thin film significantly suppresses the generation of LiOH and Li2 CO3 during both synthesis and storage, thereby mitigating slurry gelation and gas evolution and improving the cycle stability. Abstract : A simple in situ method to control the residual lithium in high‐nickel lithium layered oxide is designed. Residual Li2 O (the origin of LiOH and Li2 CO3 ) is preemptively converted into the Li2 SO4 thin film by injecting SO2 gas during calcination. This method suppresses the generation of LiOH and Li2 CO3 during both synthesis and storage, thereby mitigating slurry gelation and gas evolution and improving cycle stability.